Dendrobium jinghuanum, a new orchid species from Yunnan, China: evidence from both morphology and DNA - Zheng, Bao-Qiang; Zou, Long-Hai; Wan, Xiao; Wang, Yan (Phytotaxa, 2020)
A new orchid species, Dendrobium jinghuanum (Epidendroideae, Orchidaceae), from Yunnan Province, China, is described and illustrated based on morphological and molecular data. Morphological investigations indicated this new orchid is similar to D. bensoniae, D. crystallinum, and D. wardianum, but it can be differentiated easily from them by associated characteristics: 7-veined sepals, 9-veined petals, a chestnut blotch on either side of lip disk, an anther cap with distinct crystalline papillae, and stems without swollen nodes. Molecular phylogeny analyses showed that D. jinghuanum is a member of section Dendrobium s.l. and sister to D. bensoniae but not D. crystallinum or D. wardianum.